Ratio of roughage to concentrate for fattening heifers. - Richardson, D.; Smith, E.F.; Cox, R.F.; Keating, E.K. (Kansas Agricultural Experiment Station, 2012)
Fifty Hereford heifers were divided into five lots as equally as possible on the basis of weight, size, conformation, and previous treatment. These heifers were wintered as calves on the following rations: (1) alfalfa hay, (2) Atlas sorghum silage. 2 pounds of corn and 1 pound of soybean oilmeal pellets, (3) Atlas sorghum silage and 3 pounds of special supplement, (4) prairie hay, 4.9 pounds of corn and 1.25 pounds of soybean oilmeal pellets, (5) corn cobs, 4.9 pounds of corn and 1.9 pounds of soybean oilmeal pellets. There were 10 animals on each of these rations. Each of the five lots in this experiment had two heifers from each of the five previous treatments. A mixture of one-half alfalfa and one-half bromegrass hay which had been chopped to facilitate mixing was used as the roughage. Coarsely ground corn and milo grain were used as the concentrates except in Lots 2. 4, and 5, where soybean oilmeal was added to maintain the same level of protein in all lots. Chemical analyses of feeds used in this experiment are shown in Table No. 36 in the back of this circular. Water. salt, and ground limestone were provided free choice at all times.
Keywords: Beef; Roughage; Concentrate; Gain